The Impact of Digital Technology on social media platforms and (Virtual reality technologies) on the Promotion and Marketing of Archaeological and Historical Sites in the Emirate of Sharjah: The Site of Mleiha as a Case Study - AlHajeri, Hooria; Maksoud, Aref; Al-Areshi, Mukhtar (Al-Adab Journal, 2024)
The Emirate of Sharjah is rich in a great cultural and civilizational history, derived from the wise leadership - His Highness Sheikh Dr. Sultan bin Muhammad Al Qasimi - through his direct supervision of reviving historical sites to preserve the historical and cultural heritage, through the establishment of an independent body concerned with antiquities to protect them from extinction, and make The Emirate is a proud historical and cultural edifice. The archaeological and historical sites were not promoted and marketed in innovative and attractive ways, and digital and virtual technology were not exploited in them to show the historical beauty in them and to see all its archaeological features as if you were living those ages and wandering between those places and enjoying them.This thesis aims to shed light on the management of archaeological sites and urban heritage, and to highlight their historical, civilizational and cultural importance, by enhancing the role of digital technology and virtual reality, to ensure the sustainability of these sites for future generations, in innovative ways that keep pace with accelerators, and accept the inclusion of digital technology represented in (application AR-VR-Hologram-360), Attracting archaeological tourism, and thus transforming the archaeological sites in the emirate into cultural destinations, commercial and economic value, with ancient historical value and competitive tourism sites, according to the requirements of the digital age, and strengthening the historical site of Al-Mleiha (case study) as an innovative historical tourist destination through the integration of digital technology. The concept of virtual reality technologies and harnessing it in promoting it, activating the role of virtual trips, and making it an innovative competitive tourism site.